2011
DOI: 10.1016/j.febslet.2011.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of the tumor suppressor DRO1 by AIB1

Abstract: Edited by Angel NebredaKeywords: DRO1 Apoptosis AIB1 Golgi Extracellular matrix a b s t r a c t Using transcriptomic gene expression profiling we found tumor suppressor DRO1 being repressed in AIB1 transgenic mice. In agreement, AIB1 represses DRO1 promoter and its expression levels inversely correlate with DRO1 in several cancer cell lines and in ectopic and silencing assays. Estrogen modulators treatment showed a regulation in an estrogen receptor-dependent fashion. Importantly, DRO1 overexpression resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Consistently, downregulation of DRO1/CCDC80 upon oncogenic activation has been observed in mammary epithelial and carcinoma cells, both overexpressing the oncogene AIB1, and in U2OS osteosarcoma cells transfected with v-H-Ras and v-Src [7]. In contrast, in PC E1A thyroid cells, introduction of polyoma middle-T or v-src oncogenes had no effect on DRO1/CCDC80 expression level [6].…”
Section: Expression Pattern Of Dro1/ccdc80mentioning
confidence: 62%
See 2 more Smart Citations
“…Consistently, downregulation of DRO1/CCDC80 upon oncogenic activation has been observed in mammary epithelial and carcinoma cells, both overexpressing the oncogene AIB1, and in U2OS osteosarcoma cells transfected with v-H-Ras and v-Src [7]. In contrast, in PC E1A thyroid cells, introduction of polyoma middle-T or v-src oncogenes had no effect on DRO1/CCDC80 expression level [6].…”
Section: Expression Pattern Of Dro1/ccdc80mentioning
confidence: 62%
“…Converse results on the effect of β-Estradiol on DRO1/CCDC80 expression have been obtained by Ferragud and colleagues. They have shown that addition of β-Estradiol to the medium of human mammary carcinoma cells represses DRO1/CCDC80 expression, whereas treatment with antiestrogens leads to DRO1/CCDC80 induction [7]. Thus, further studies are needed to elucidate the role of DRO1/CCDC80 in mammary carcinogenesis.…”
Section: Expression Pattern Of Dro1/ccdc80mentioning
confidence: 97%
See 1 more Smart Citation
“…Further investigation revealed that DROI plays an important role in adipogenesis through downregulating Wnt/β-catenin signaling and inducing C/EBPα and PPARγ (75). The expression of DROI was significantly reduced in mouse mammary epithelial cells or human primary cultures overexpressing AIB1 (72). Furthermore, DROI expression levels decreased in MCF-7 cells treated with estrogen but increased when treated with tamoxifen.…”
Section: Influence Of Aib1 On Tumor Suppressor Gene and Cancermentioning
confidence: 94%
“…For example, knockdown of AIB1 by siRNA in human chronic myeloid leukemia K562 cells reduces activation of NF-κB signaling, ultimately leading to apoptosis (70), while overexpression of AIB1 in human embryonic kidney 293 (HEK293) cells has the reverse effect (71). A study by Ferragud et al (72) revealed that AIB1 acts as a negative regulator for DROI, a tumor suppressor gene that was first identified as upregulated in brown adipose tissue of mice deficient in bombesin receptor subtype-3 (73). The function of DROI as a tumor suppressor gene was later demonstrated when its expression was shown to be highly reduced in colon and pancreatic cancers (74).…”
Section: Influence Of Aib1 On Tumor Suppressor Gene and Cancermentioning
confidence: 99%